Crystal structure of fingolimod hydrochloride, C19H34ClNO2. Issue 3 (12th August 2015) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of fingolimod hydrochloride (C19 H34 ClNO2 ) has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Fingolimod hydrochloride crystallizes in space group P 21 / n (#14) with a = 7.137 53(5), b = 5.957 98(4), c = 49.5196(4) Å, β = 91.0808(7)°, V = 2105.46(2) Å 3, and Z = 4. The structure consists of a "lipid bilayer" packing. The polar ends of the molecules make O–H···Cl and N–H···Cl hydrogen bonds to the chloride anion, and the octyl side chains pack adjacent to each other. The hydrogen bonds form three types of chains with graph sets C1, 2(7), C1, 2(7), and C1, 2(8). The result is a complex chain of hydrogen bonds parallel to the b -axis. The powder pattern has been submitted to ICDD for inclusion in future releases of the Powder Diffraction File™.